Dependence of the Startle Response on Temporal and Spectral Characteristics of Acoustic Modulatory Influences in Rats and Gerbils - Steube, Natalie; Nowotny, Manuela; Pilz, Peter K. D.; Gaese, Bernhard H. (Frontiers in Behavioral Neuroscience, 2016)
The acoustic startle response and its modulation by non-startling prepulses, presented shortly before the startle-eliciting stimulus, is a broadly applied test paradigm to determine changes in neural processing related to auditory or psychiatric disorders. Modulation by a gap in background noise as a prepulse is especially used for tinnitus assessment. However, the timing and frequency-related aspects of prepulses are not fully understood. The present study aims to investigate temporal and spectral characteristics of acoustic stimuli that modulate the acoustic startle response in rats and gerbils. For noise-burst prepulses, inhibition was frequency-independent in gerbils in the test range between 4 and 18 kHz. Prepulse inhibition by noise-bursts in rats was constant in a comparable range (8 to 22 kHz), but lower outside this range. Purely temporal aspects of prepulse–startle-interactions were investigated for gap-prepulses focusing mainly on gap duration. While very short gaps had no (rats) or slightly facilitatory (gerbils) influence on the acoustic startle response, longer gaps always had a strong inhibitory effect. Inhibition increased with durations up to 75 ms and remained at a high level of inhibition for durations up to 1000 ms for both, rats and gerbils. Determining spectral influences on gap-prepulse inhibition revealed that gerbils were unaffected in, again, the limited frequency range tested (4–18 kHz). The more detailed analysis in rats revealed a variety of frequency-dependent effects. Gaps in pure-tone background elicited constant and high inhibition (around 75%) over a broad frequency range (4–32 kHz). For gaps in noise-bands, on the other hand, a clear frequency-dependency was found: Inhibition was around 50% at lower frequencies (6–14 kHz) and around 70% at high frequencies (16–20 kHz). This pattern of frequency-dependency in rats was specifically resulting from the inhibitory effect by the gaps, as revealed by detailed analysis of the underlying startle amplitudes. An interaction of temporal and spectral influences, finally, resulted in higher inhibition for 500-ms gaps than for 75-ms gaps at all frequencies tested. Improved prepulse paradigms based on these results are well suited to quantify the consequences of central processing disorders.